Planning is the main success factor in obtaining a harmonious and minimally invasive result with direct anterior restorations after orthodontic treatment - O. Naidyonova (LLC "Endo Press", 2020)
Orthodontic treatment may lead to the patients dissatisfaction with the anterior teeth microesthetics. This case report demonstrates the reasons of anterior direct restorations choice after digital mock-ups and patient compliance. The clinical procedures improved the patient's oral esthetics of teeth. At one week recall the general outlook of the maxillary anterior teeth was considered natural and esthetical. Clinically, restorations demonstrated no discolorations and dispolishing.